Multimodal approach for pediatric mandibular fractures- A case series - Gehlot, Neelima; Gupta, D.S; Pillai, Sooraj S.; Singh, Snigdha (Journal of Case Reports in Dental Medicine, 2024)
Objective: The management of facial fractures varies due to variety of reasons in the pediatric age groups. The clinicians should therefore atune themselves in managing pediatric patients and the variations thereof. Every modality mentioned in the literature has its own advantages and disadvantages. The right choice of treatment by clinicians depends on their knowledge of pediatric anatomy, physiology, age dependent bone growth, type and extend of fractures.Methods: Patients reporting to the OPD of Oral and Maxillofacial department falling under the age group of upto 13 years of age and seeking treatment for mandibular fractures were studied.Results: Three different modalities of treatment in the form of circummandibular wiring, intermaxillary fixation and open reduction and internal fixation were rendered to the patients considering various factors such as the age, location of fracture line, status of occlusion and dentition of the patient. All the three modalities showed good results in the form of adequate reduction and no post-op complications.Conclusion: Pediatric trauma are a challenging entity for the surgeon. The choice of ideal treatment modalityultimately depends on presence of tooth buds and maintanence of uninterupted growth of the jaw bone. Thus a well thought-of and customised treatment plan should be devised for each individual case.